Characterization of Additive Function in Hermitian Banach *-Algebras - Goutam Das; Nilakshi Goswami (Mathematics and Computer Science: Contemporary Developments Vol. 1, 2024)
The aim of this paper is to give some new charaterizations of additive functions in the tensor product of two hermitian Banach *-algebras. Our results extend Vukman’s work on Cauchy functional equation in hermitian Banach *-algebras to the projective tensor product. An example is provided in support of our result.